The Role of Media Pressure in Promoting Transparency of Local Governments - Beatriz CUADRADO-BALLESTEROS; Jennifer MARTÍNEZ-FERRERO; José-Valeriano FRÍAS-ACEITUNO; Isabel-María GARCÍA-SÁNCHEZ (Transylvanian Review of Administrative Sciences, 2017)
This paper analyses the role of media pressureon the level of public transparency of localgovernments. Making use of a sample composedby 110 Spanish cities for the 2008-2010period, the results show that local governmentstend to be more transparent under media pressure,especially in relation to information abouteconomic, fi nancial, urbanism and public worksissues.Additionally, we take into account the electoralmoment, since the analysis of the ways inwhich public affairs are conducted is still superiorwhen elections are approaching. Empiricalresults indicate that media plays a fundamentalrole in that moment because governments arewilling to decrease the level of information transparency.